Introduction to Nanomaterials in Medicine - Rabiee, Mohammad; Rabiee, Navid; Salarian, Reza; Rabiee, Ghazal (IOP Concise Physics,, 2019)
Advancement in the field of nanotechnology has revolutionized the field of medicines and pharmaceuticals in the twentieth century. This book, considering the importance of nanomaterials and their application in medicine, as well as the significant growth of biomaterials in research fields, introduces the variables law (Rabiee's theory) for the implementation of this research and the establishment of a proper strategy.- Resumé vydavatel